Modelling an unhealthy behaviour index among school-going adolescents in Timor-Leste: a two-part approach - Yong, Kang Cheah; Chee, Cheong Kee; Kuang, Kuay Lim; Lay, Kim Tan; Yoon, Ling Cheong; Lim, Jia Hui (Universiti Kebangsaan Malaysia, 2025)
The burden of unhealthy behaviours in the adolescent population is a worldwide public health concern. This study develops an unhealthy behaviour index and examines its associated factors within a large sample of adolescents from Timor-Leste. The data of 3455 adolescents from a nationally representative sample were analysed. The unhealthy behaviour index was developed based on the number of involvements in unhealthy behaviours (consumption of soft drink and fast food, low intake of fruit and vegetables, physical inactivity, smoking, alcohol drinking, illicit drug use). A two-part model was applied to assess the influences of demographic, environmental, personal and parental factors on the participation decisions of unhealthy behaviours and the unhealthy behaviour index. Parental closeness was associated with participation decisions. Age, being involved in physical fights, suicide attempt and parental connectedness were correlated with unhealthy behaviour index. Bullying victimisation and truancy affected both participation and index. There were interaction effects of gender and loneliness on the unhealthy behaviour index. Adolescents who engage in unhealthy behaviours are more likely to be younger, be involved in physical fights, experience bullying, attempt suicide, play truant and have no parental closeness and connectedness. The specific policy recommendations include discouraging male adolescents who do not encounter loneliness as well as those in lower-secondary education from indulging in unhealthy lifestyles. Additionally, parents should collaborate with educators on monitoring adolescents’ environmental stressors, mental health condition and class attendance, and be prepared to provide support in a timely manner.